2004
DOI: 10.1074/jbc.m400933200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adenovirus Type 2 Early Region 4 ORF4 Cytoplasmic Death Function by Direct Binding to Src Kinase Domain

Abstract: Adenovirus type 2 (Ad2) early region 4 ORF4 (E4orf4) triggers a major death pathway that requires its accumulation in cellular membranes and its tyrosine phosphorylation. This program is regulated by Src family kinases and triggers a potent ZVAD (benzyloxycarbonyl-VAD)-and Bcl2-resistant cell death response in humantransformed cells. How E4orf4 deregulates Src-dependent signaling is unknown. Here we provide strong evidence that a physical interaction requiring the kinase domain of Src and the arginine-rich mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 56 publications
(79 reference statements)
3
73
1
Order By: Relevance
“…Of the known cellular targets of E4-ORF4, c-Src and PP2A seem the most likely to mediate E4-ORF4's effects on mTOR activation, given their well established roles in cellular signaling cascades. E4-ORF4 has been shown to bind to the c-Src kinase domain in vitro, 17 and to affect the tyrosine phosphorylation of c-Src substrates in transfected cells. 18 c-Src has previously been reported to activate mTOR, 19 although these effects are thought to be mediated by c-Src induced activation of the growth factor/PI3-kinase signaling pathway.…”
Section: Adenovirus Encodes Early Proteins That Mimic Nutrient and Grmentioning
confidence: 99%
“…Of the known cellular targets of E4-ORF4, c-Src and PP2A seem the most likely to mediate E4-ORF4's effects on mTOR activation, given their well established roles in cellular signaling cascades. E4-ORF4 has been shown to bind to the c-Src kinase domain in vitro, 17 and to affect the tyrosine phosphorylation of c-Src substrates in transfected cells. 18 c-Src has previously been reported to activate mTOR, 19 although these effects are thought to be mediated by c-Src induced activation of the growth factor/PI3-kinase signaling pathway.…”
Section: Adenovirus Encodes Early Proteins That Mimic Nutrient and Grmentioning
confidence: 99%
“…E4orf4 is also toxic in yeast (Saccharomyces cerevisiae), and this effect is largely abrogated in yeast lacking CDC55, the B55 ortholog (22)(23)(24)(25)(26)(27)(28). E4orf4 also interacts with Src nonreceptor tyrosine kinases (29)(30)(31). This interaction results in actin remodeling and morphological changes and may contribute to cell death (32,33).…”
mentioning
confidence: 99%
“…Furthermore, polyoma MT was also found to interact with c-SRC [36] leading to its activation [37]. Moreover, it was reported that adenovirus E4orf4 can interact with both c-SRC and PR55a independently and that the interaction with c-SRC is required for E4orf4 to induce apoptosis [46,52]. Overexpression of E4orf4 phenocopies loss of PR55 in yeast [53], allowing the possibility that inhibition of PR55a is a prerequisite for E4orf4-induced apoptosis in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both polyoma MT antigen and adenovirus E4orf4 were previously shown to interact with both c-SRC and PR55a independently, but the relevance of these interactions remained elusive [46][47][48]. To further address the functional relationship between PR55 and c-SRC, we asked whether PR55c could physically interact with c-SRC.…”
Section: Pr55c Interacts With C-srcmentioning
confidence: 99%